Auri cupidine immensa flagrantes, czyli o koczowniczej żądzy dóbr - Paroń, Aleksander (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
This article aims to reflect on the history of conflicts between farmers and their nomadic neighbours. From one perspective this shows the circumstances in which the actual experiences which were subsequently included in historical accounts first originated; while from the other it indicates common conditions for the development of diverse traditions which define the manner in which nomadic peoples are perceived by settled nations.
Keywords: nomads; the Great Steppe; Chinese historiography; Byzantine historiography; Sima Qian; Xiongnu; Pechenegs; Mongolians